Islamic Perspective on Eye Protection from Occupational Radiation Exposures in Interventional Fluoroscopy Procedures: A Review Article - Ahmad Radzi, Halimatussa'diah; Sohaimi, Norhanna; Md Ralib, Ahmad Razali (IIUM Medical Journal Malaysia, 2022)
The healthcare staff in interventional fluoroscopy room are exposed to the scattered-radiation from the patient during the procedures. Excessive occupational radiation exposures to their eyes are associated with the formation of radiation-induced cataracts. Therefore, recommendations are set-up to reduce the occupation eye exposure but are often overlooked. Thus, there is a need to incorporate additional value into the recommendations. This review is conducted to incorporate the Islamic perspectives into the recommendations on the eye protection from occupational radiation exposures. Common themes were derived from the recommendations as stated in several guidelines and articles. The relevant Islamic perspective were then identified and linked. The main themes are the responsibilities of the staff in protecting their eyes and the responsibilities of the employers to ensure that their staff are protected. There were several subthemes identified for each main theme. The relevant Islamic perspectives which are related to the identified themes, eyes and concept of radiation protection were discussed in this review. The incorporation of Islamic perspective is an effort to motivate the Muslim staff and employers to see additional values and thus follow the recommendations on the eye lens protection.